The Effect of Zinc Supplementation of Lactating Rats on Short-Term and Long-Term Memory of Their Male Offspring - Mohammad Karami; Simin EhsaniVostacolaee; Ali Ahmad Moazedi; Anahita Nosrati (Tabriz University of Medical Sciences, 2013)
Background: In this study the effect of zinc chloride (ZnCl2) administration on the short-term and long-term memory of rats were assessed. Methods: We enrolled six groups of adult female and control group of eight Wistar rats in each group. One group was control group with free access to food and water, and five groups drunk zinc chloride in different doses (20, 30, 50, 70 and 100 mg/kg/day) in drinking water for two weeks during lactation .One month after birth, a shuttle box used to short- term and long-term memory and the latency in entering the dark chamber as well. Results: This experiment showed that maternal 70 mg/kg dietary zinc during lactation influenced the working memory of rats' offspring in all groups. Rats received 100 mg/kg/day zinc during lactation so they had significant impairment in working memory (short-term) of their offspring (P<0.05). There was no significant difference in reference (long-term) memory of all groups. Conclusion: Drug consumption below70 mg/kg/day zinc chloride during lactation had no effect. While enhanced 100 mg/ kg/ day zinc in lactating rats could cause short-term memory impairment.